Advancements, challenges, and implications for navigating the autonomous vehicle revolution - Hossain, Md Naeem; Rahman, M. M.; Ramasamy, Devarajan; Kadirgama, Kumaran; Noor, M. M. (Faculty Mechanical Engineering, UMP, 2024)
The deployment of self-driving cars has significantly impacted society, offering several benefits such as better passenger safety, convenience, reduced fuel consumption, minimised traffic congestion and accidents, cost savings, and improved reliability. With the development of automated driving systems, autonomous vehicle technology has progressed from human-operated vehicles to conditional automation, utilising an array of sensors to constantly observe their surroundings for potential hazards. However, it is crucial to highlight that full autonomy has not yet been reached, and there are several problems involved with this revolutionary technology. This article explores the advancements, challenges, and implications inherent in the widespread adoption of autonomous vehicles. Recent advancements in sensor technology (cameras, RADARs, LiDARs, and ultrasonic sensors), artificial intelligence, the Internet of Things, and blockchain are just some of the topics covered in this article regarding autonomous vehicle development. These advancements are critical to evolving and incorporating autonomous vehicles into the transportation ecosystem. Furthermore, the analysis emphasises the considerable problems that must be overcome before self-driving cars can be widely adopted. These difficulties include security, safety, design, performance, and accuracy. Focused solutions such as increasing cybersecurity protections, refining safety standards, optimising vehicle design, enhancing performance capabilities, and assuring correct perception and decision-making are proposed to tackle these challenges. Lastly, autonomous cars have great promise for transforming transportation systems and improving a wide range of areas of our lives. Nevertheless, successful implementation requires overcoming existing difficulties and pushing technological innovation’s limits. By solving these problems and capitalising on artificial intelligence, the Internet of Things, and blockchain breakthroughs, we can navigate the autonomous car revolution and realise its full potential for a safer, more efficient, and sustainable future.